Analysis of Song "Tanganku Na Metmet" by Using Translation Techniques into English - Marudut Bernadtua Simanjuntak; Irma Rasita Gloria Barus; Ira Resmayasari (UICELL, 2020)
This study aims to analyze "Ende Tanganku Na Metmet", which is a traditional song in the Toba Batak language by using translation techniques into English. Translation techniques are the methods used by translators to convey messages from the source language to the translation language. Translation techniques can explain the essence of the object of translation which is applied at the level of words, phrases, clauses, or sentences. The theory used is the Newmark translation technique. This research method is descriptive analysis. The results of this study, the translation techniques used by the translators are 1) transposition, intrasystem shift (intra-category shift), 2) modulation, consisting of shifting the scope of meaning. 3) Omission. 4) Culture Understanding